Analisis Hubungan Daya Ledak Otot Tungkai dengan Kemampuan Montong Dollyo Chagi Atlet Taekwondo - Zulman Zulman; Sandra Dewi; Weny Sasmitha (Jurusan Kepelatihan, Fakultas Ilmu Keolahragaan, Universitas Negeri Padang, 2021)
The problem in this research is the low montong dollyo chagi ability of athletes of Taekwondo Dojang Head of Sub-District VII Koto Sungai Sariak, Padang Pariaman Regency. This study aims to determine how much the variable contribution of leg muscle explosive power to the ability of montong dollyo chagi. The population in this study were athletes of Taekwondo Dojang Head VII Koto Sungai Sariak, Padang Pariaman Regency, the sample was drawn using purposive sampling technique, so that 11 people were obtained as a sample. The data were collected using a standing board jump test for the explosive power of the leg muscles, and the dollyo chagi kick test with a dollyo chagi speed test with a test time of 10 seconds. The data analysis was processed using the product moment correlation technique. Based on the product moment correlation calculation, the results showed that there was a significant relationship between leg muscle explosive power and the athlete's montong dollyo chagi ability with a contribution of 63.68%.